2020
DOI: 10.1039/c9fo01813a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of α-amylase inhibitor enriched-extract from white common beans (Phaseolus vulgaris L.) associated with the modulation of gut microbiota composition in high-fat diet-induced obese rats

Abstract: α-Amylase inhibitors (α-AI) have great potential to treat obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 48 publications
1
53
0
1
Order By: Relevance
“…A number of animal studies, with intervention durations ranging from 14 to 238 days, have explored the effects of WKBE on body weight and composition ( Table 1 ). Although not a universal finding [ 29 , 30 , 31 ], several studies have demonstrated significant reductions in body weight or reduced weight gain following the administration of WKBE versus a control [ 32 , 33 , 34 , 35 , 36 , 37 ]. For example, Song et al [ 37 ] reported a significant attenuation in weight gain and reduced visceral fat in mice after 98 days of supplementation with 50 mg/kg/d WKBE alongside a high-fat diet when compared with a high-fat diet alone.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of animal studies, with intervention durations ranging from 14 to 238 days, have explored the effects of WKBE on body weight and composition ( Table 1 ). Although not a universal finding [ 29 , 30 , 31 ], several studies have demonstrated significant reductions in body weight or reduced weight gain following the administration of WKBE versus a control [ 32 , 33 , 34 , 35 , 36 , 37 ]. For example, Song et al [ 37 ] reported a significant attenuation in weight gain and reduced visceral fat in mice after 98 days of supplementation with 50 mg/kg/d WKBE alongside a high-fat diet when compared with a high-fat diet alone.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…Interestingly, recent findings from Shi et al [ 32 ] suggest that the anti-obesity effects of WKBE may be both dose- and duration-dependent. The authors reported a significant reduction in body weight in male Sprague Dawley rats receiving the largest dose of WKBE (1.5% addition) for 42 days.…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
See 3 more Smart Citations